2013
DOI: 10.1021/es303808b
|View full text |Cite
|
Sign up to set email alerts
|

Blood and Urinary Bisphenol A Concentrations in Children, Adults, and Pregnant Women from China: Partitioning between Blood and Urine and Maternal and Fetal Cord Blood

Abstract: Limited information exists on exposure to bisphenol A (BPA) by children, adults, and pregnant women in China. In the present study, we determined BPA concentrations in whole blood collected from 10 children (1-5 years), 40 women (30 pregnant and 10 nonpregnant), and 30 fetuses (i.e., cord blood). Further, to evaluate the relationship between urinary and blood BPA concentrations, paired specimens of blood and urine (n = 50 pairs) were collected from an adult population. BPA was found in 46% of all blood samples… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
68
9

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 173 publications
(91 citation statements)
references
References 43 publications
14
68
9
Order By: Relevance
“…Slightly lower concentration was observed in pregnant women (0.60 ng/ml, M±SD = 3.58±4.25 ng/ml, range: < 0.10-29.0 ng/ml), adults (0.11 ng/ml, M±SD = 0.20±0.18 ng/ml, range: < 0.10-2.27 ng/ml), fetal cord blood (0.08 ng/ml, M±SD = 0.13±0.12 ng/ml, range: < 0.10-0.79 ng/ml). The lowest concentration of BPA was observed in fetuses [86]. Probably fluids given by a drip may also provide BPA to the blood of pregnant women.…”
Section: Absorption and Distributionmentioning
confidence: 95%
See 2 more Smart Citations
“…Slightly lower concentration was observed in pregnant women (0.60 ng/ml, M±SD = 3.58±4.25 ng/ml, range: < 0.10-29.0 ng/ml), adults (0.11 ng/ml, M±SD = 0.20±0.18 ng/ml, range: < 0.10-2.27 ng/ml), fetal cord blood (0.08 ng/ml, M±SD = 0.13±0.12 ng/ml, range: < 0.10-0.79 ng/ml). The lowest concentration of BPA was observed in fetuses [86]. Probably fluids given by a drip may also provide BPA to the blood of pregnant women.…”
Section: Absorption and Distributionmentioning
confidence: 95%
“…Similarly, among younger children, relatively higher daily rates of excretion of BPA (< 70 ng/kg b.w./24 h) were observed than in older children and 17-21-year-old adolescents, < 1 ng/ml and < 30 ng/kg b.w./24 h, respectively. Zhang et al (2013) [86] studied children (1-5-yearsold: N = 10) and women (pregnant: N = 30, and nonpregnant: N = 10), and fetuses (N = 30) from whom blood samples were collected. The highest concentration of BPA in blood was determined in children (2.60 ng/ml, M ± standard deviation (SD) = 3.18±1.16 ng/ml, range: 1.20-8.76 ng/ml).…”
Section: Absorption and Distributionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have reported on the exposure of humans to BPA (Calafat et al, 2008;Vandenberg et al, 2010;Zhang et al, 2011Zhang et al, , 2013. BPA has been reported to occur in a wide range of environmental samples including sediment, indoor dust, surface water, and drinking water (Staples et al, 1998;USEPA, 2010;Liao et al, 2012d;Lee et al, 2013;Wu et al, 2013;Zhang et al, 2013;Selvaraj et al, 2014;Colin et al, 2014;Lee et al, 2015). Human and environmental exposure to BPA is a concern because studies have shown that this chemical is a potential endocrine disruptor (Tsai, 2006;Vandenberg et al, 2009;Rogers et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Due to the diverse uses of BPA in consumer products, it has been regularly detected in a wide range of environmental matrices, including air, water, sewage sludge and sediments (Huang et al, 2012;Lee et al, 2013;Xiong et al, 2015), even human blood and tissues (Vandenberg et al, 2010;Zhang et al, 2013). Several studies have reported that BPA is a potential endocrine disruptor (Rogers et al, 2013;Vandenberg et al, 2010).…”
Section: Introductionmentioning
confidence: 99%